Modeling of the spatial structure of eukaryotic ornithine decarboxylases. - Grishin, N. V. (Cold Spring Harbor Laboratory Press, 1995)
We used sequence and structural comparisons to determine the fold for eukaryotic ornithine decarboxylase, which we found is related to alanine racemase. These enzymes have no detectable sequence identity with any protein of known structure, including three pyridoxal phosphate-utilizing enzymes. Our studies suggest that the N-terminal domain of ornithine decarboxylase folds into a beta/alpha-barrel. Through the analysis of known barrel structures we developed a topographic model of the pyridoxal phosphate-binding domain of ornithine decarboxylase, which predicts that the Schiff base lysine and a conserved glycine-rich sequence both map to the C-termini of the beta-strands. Other residues in this domain that are likely to have essential roles in catalysis, substrate, and cofactor binding were also identified, suggesting that this model will be a suitable guide to mutagenic analysis of the enzyme mechanism.